Smart grid security : First International Workshop, SmartGridSec 2012, Berlin, Germany, December 3, 2012, Revised Selected Papers - Cuellar, Jorge (Lecture Notes in Computer Science, 2013)
The engineering, deployment and security of the future smart grid will be an enormous project requiring the consensus of many stakeholders with different views on the security and privacy requirements, not to mention methods and solutions. The fragmentation of research agendas and proposed approaches or solutions for securing the future smart grid becomes apparent observing the results from different projects, standards, committees, etc, in different countries. The different approaches and views of the papers in this collection also witness this fragmentation. This book contains three full-paper length invited papers and 7 corrected and extended papers from the First International Workshop on Smart Grid Security, SmartGridSec 2012, which brought together researchers from different communities from academia and industry in the area of securing the Future Smart Grid and was held in Berlin, Germany, on December 3, 2012.